An insight into the adsorption and electrochemical processes occurring during the analysis of copper and lead in wines, using an electrochemical quartz crystal nanobalance - Yamasaki, Alzira (2019)
Copper and lead in wine were quantified by anodic stripping voltammetry (ASV), performed onto the gold electrode of a piezoelectric quartz crystal. Both current or mass changes could be used as analytical signals, without a statistical difference in the results (α=0.05). However, the plot of mass vs. potential provided an in depth understanding of the electrochemical processes and allowed studying adsorption phenomena. Copper interaction with fructose is an example of a process which was not possible to ignore by observing the mass change on the gold electrode of the piezoelectric quartz crystal.